2019
DOI: 10.3897/zse.95.29487
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Bungona in Turkey (Ephemeroptera, Baetidae): an unexpected biogeographic pattern within a pantropical complex of mayflies

Abstract: By using an integrative approach, we describe a new species of mayfly, Bungona (Chopralla) ponticasp. n., from Turkey. The discovery of a representative of the tropical mayfly genusBungonain the Middle East is rather unexpected. The new species shows all the main morphological characters of the subgenus Chopralla, which has its closest related species occurring in southeastern Asia. Barcoding clearly indicated that the new species represents an independent lineage isolated for a very long time from other membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…At the same time, they accepted the interpretation of Bungona narilla proposed by Suter and Pearson (2001), and based on this, moved all Centroptella and Chopralla to the genus Bungona but treated these three taxa as subgenera. In accordance with this classification, Bungona (Centroptella) papilionodes Marle, Salles & Gattolliat, 2016 and Bungona (Chopralla) bintang Marle, Salles & Gattolliat, 2016 were described from Borneo; Bungona (Chopralla) pontica Sroka, Godunko & Gattolliat in Sroka et al 2019 was described from Turkey; Bungona (Centroptella) ovata Shi & Tong, 2019, Bungona (Centroptella) quadrata Shi & Tong, 2019 and Bungona (Chopralla) bifida Shi & Tong, 2019 were described from China. Most descriptions were based on larvae only and, hence, lack some important taxonomic characters.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…At the same time, they accepted the interpretation of Bungona narilla proposed by Suter and Pearson (2001), and based on this, moved all Centroptella and Chopralla to the genus Bungona but treated these three taxa as subgenera. In accordance with this classification, Bungona (Centroptella) papilionodes Marle, Salles & Gattolliat, 2016 and Bungona (Chopralla) bintang Marle, Salles & Gattolliat, 2016 were described from Borneo; Bungona (Chopralla) pontica Sroka, Godunko & Gattolliat in Sroka et al 2019 was described from Turkey; Bungona (Centroptella) ovata Shi & Tong, 2019, Bungona (Centroptella) quadrata Shi & Tong, 2019 and Bungona (Chopralla) bifida Shi & Tong, 2019 were described from China. Most descriptions were based on larvae only and, hence, lack some important taxonomic characters.…”
Section: Introductionmentioning
confidence: 74%
“…Besides these formal rules, the Code requires maintainance of prevailing usage of the taxa names which can be done only under plenary power of the Commission (paragraph 75.6). In this case, referring to prevailing usage is impossible, because there are only six publications where the species name liebenauae [Centroptella] has been mentioned (Soldán et al 1987;Soldán 1991;Salles et al 2016;Sroka et al 2019;Shi and Tong 2019). Among them, reports of larvae under this name given by Soldán (1991) and by Shi and Tong (2019) do not contain original taxonomic conclusions.…”
Section: Reasons For the Neotype Designationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the genus Bungona has been erected more than half a century since 1957, the systematic position of Bungona has scarcely been discussed until Salles et al (2016) who clarified the relationship between Cloeodes Traver, 1938 and related genera including Bungona by phylogenetic analysis, with resultant clarification of much taxonomic confusion. According to their concept of the Cloeodes complex, Cloeodes is restricted to the New World, while Bungona is the only genus among the Cloeodes complex present in the Middle East, Asia and Australasian regions (Salles et al 2016;Sroka et al 2019). At present, the genus Bungona is composed of three subgenera: Bungona, Centroptella and Chopralla, which suggested that the genus is much more diverse and widespread than originally conceived (Salles et al 2016;Marle et al 2016;Sroka et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to their concept of the Cloeodes complex, Cloeodes is restricted to the New World, while Bungona is the only genus among the Cloeodes complex present in the Middle East, Asia and Australasian regions (Salles et al 2016;Sroka et al 2019). At present, the genus Bungona is composed of three subgenera: Bungona, Centroptella and Chopralla, which suggested that the genus is much more diverse and widespread than originally conceived (Salles et al 2016;Marle et al 2016;Sroka et al 2019). The species of Bungona in China are poorly documented, only two species have been reported : B.…”
Section: Introductionmentioning
confidence: 99%